2006
DOI: 10.1097/01.brs.0000245902.93084.12
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Inserting Atlas Lateral Mass Screws via the Posterior Arch

Abstract: Our results suggest that although only a small percentage of patients can accept a screw that is directly inserted via the posterior-lateral arch into the lateral mass, the notching technique is possible in the vast majority of patients. To our knowledge, this is the largest study to examine the possibility of using the posterior-lateral arch as the starting point for these screws. Our results suggest that alternative starting points for these screws are possible in a large percentage of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 1 publication
1
64
0
20
Order By: Relevance
“…We found that the average EMH of all the atlas pedicles was 4.43 mm, which was in consistence with the study of Tan et al [2] and Ma et al [3], smaller than the data of Christensen et al [9], and greater than the result of Lee et al [10]. 23.3 % of the patients had EMH of the C1 pedicle of \4 mm, which indicated that 23.3 % of the population was not feasible for C1 pedicle screw placement because in order to obtaining excellent mechanical performance for the internal fixation construct, the size of the screws commonly used in clinical practice was 3.5 mm and a minimum of 4 mm of bone thickness would be required.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the average EMH of all the atlas pedicles was 4.43 mm, which was in consistence with the study of Tan et al [2] and Ma et al [3], smaller than the data of Christensen et al [9], and greater than the result of Lee et al [10]. 23.3 % of the patients had EMH of the C1 pedicle of \4 mm, which indicated that 23.3 % of the population was not feasible for C1 pedicle screw placement because in order to obtaining excellent mechanical performance for the internal fixation construct, the size of the screws commonly used in clinical practice was 3.5 mm and a minimum of 4 mm of bone thickness would be required.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of PP, that is, 8.3% in this study, is lower than those reported in the literatures, that is, 9.4%-26.9%. [18][19][20][21] The Indians had a significantly higher prevalence of this bony anomaly as compared to the Chinese and Malays.…”
Section: Discussionmentioning
confidence: 99%
“…Such opinions are supported by biomechanical data showing greater pull-out strength of both unicortical and bicortical C1 lateral mass screws compared with subaxial lateral mass screws. Our practice however is to aim for bicortical purchase, given the absence of adequate comparative data for rheumatoid patients, and the greater risk of screw pullout due to the tendency of the underlying rheumatoid disease to cause osteoporosis of the vertebrae (Wordsworth et al 1984, Lee et al 2006.…”
Section: C1 Lateral Mass Screw Placementmentioning
confidence: 99%